Recent advances of Sargassum pallidum in chemical and biological aspects - Lei, Ziqin; Qin, Xiaoyan; Yang, Yan; Xu, Min; Zeng, Nan (Frontiers in Pharmacology, 2025)
Sargassum pallidum (Turn.) C.Ag. (SP) is a traditional Chinese marine medicinal material known for its extensive pharmacological activities and is primarily found in coastal regions. With a long history of medicinal use in China, it is commonly employed to treat conditions such as goiter, hyperplasia of mammary glands, hypertension, and obesity. Modern research on its phytochemical metabolites has identified polysaccharides, flavonoids, and lipids as the primary metabolites derived from SP, with polysaccharides being the most extensively studied. Modern pharmacological studies have demonstrated that extracts and secondary metabolites obtained from SP exert various biological activities, including antioxidant effects, antitumor properties, hypolipidemic and hypoglycemic actions, antibacterial activity, and immunomodulatory capabilities. This review aims to serve as a theoretical reference for further utilization and development of functional foods derived from marine resources like SP, summarizing relevant literature from both domestic and international sources. Despite a comprehensive overview of chemical metabolites and pharmacological properties, existing limitations suggest the need for more precise technical tools and additional toxicological and clinical studies to ensure quality, safety, and efficacy.